Consumption Economics: Cultural Production of Needs - Rubavičius, Vytautas (Problemos, 2003)
Lithuanian society experiences today the largest social and economic transition. The main feature of this state is rapid development of consumer society and consumption economy. These processes force to look more closely at consumption phenomenon, especially at the relation between culture and consumption. Many researchers suppose that consumption is knit with the individual needs and wants. However, the scenario of unlimited economic development is based on direct link between production and needs. It means that the notion of independently determined desires is undermined. The analysis of consumption by J. K. Galbraith and J. Baudrillard results in conclusion that under the consumption capitalism all variety of needs and wants is produced together with goods. Goods and commodified services satisfy needs produced by culturalized economy. At this stage of capitalism culture becomes economic force producing wants and implementing them as higher living standards vision and also as social means of individual identity formation. In this article Baudrillardian critique of use value fetishism is used to unveil the ideological content of such concepts as "free consumer choice" and "freedom of consumption". Also some features of socialist consumption and its link with capitalist one are examined.
Keywords: culture industry; capitalism; socialism; consumption; consumer society; use value fetishism